2008
DOI: 10.1111/j.1365-2966.2008.13019.x
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of voids in the cosmic web

Abstract: We investigate the shapes and mutual alignment of voids in the large‐scale matter distribution of a Λ cold dark matter (ΛCDM) cosmology simulation. The voids are identified using the novel watershed void finder (WVF) technique. The identified voids are quite non‐spherical and slightly prolate, with axis ratios in the order of c : b : a≈ 0.5 : 0.7 : 1. Their orientations are strongly correlated with significant alignments spanning scales >30 h−1 Mpc. We also find an intimate link between the cosmic tidal field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 33 publications
8
82
0
Order By: Relevance
“…Perhaps not surprisingly, we find a slight majority of prolate voids (T average = 0.67±0.09) in agreement with the theoretical models of Platen et al (2008). Figure 5 shows the bivariate distribution of 1 versus 2 .…”
Section: Shape and Orientationsupporting
confidence: 72%
See 2 more Smart Citations
“…Perhaps not surprisingly, we find a slight majority of prolate voids (T average = 0.67±0.09) in agreement with the theoretical models of Platen et al (2008). Figure 5 shows the bivariate distribution of 1 versus 2 .…”
Section: Shape and Orientationsupporting
confidence: 72%
“…First, as with the above radius analysis, this result may be affected by cosmic variance, especially at low redshift. Second, using N-body simulations, Platen et al (2008) have shown that the ΛCDM model predicts that the orientation of voids in the distribution of dark matter haloes can be correlated for scales < 30 h −1 Mpc. On the other hand, they also find that this predicted void alignment becomes less significant for larger scales.…”
Section: Shape and Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning here how the velocity shear field is different from the tidal shear field that was widely used as a tracer of the cosmic web in the previous approaches based on the classical cosmic web theory (e.g., Bond et al 1996;Hahn et al 2007; Platen et al 2008;Forero-Romero et al 2009;Lee et al 2009;Zhang et al 2009Zhang et al , 2013. The tidal shear field defined as the second derivative of the gravitational potential is basically a linear quantity, obtained under the implicit assumption that the peculiar velocity field is curl free, whereas the velocity shear field is an extension of the tidal shear field to the nonlinear regime where the velocity field develops a curl mode (i.e., vorticity).…”
Section: Introductionmentioning
confidence: 99%
“…An order of magnitude estimate by [10] for a completely empty void (δ = −1) at z < ∼ 1 puts the comoving radius at ∼ 120h −1 Mpc. To put these dimensions in perspective, both observations [16,17] and numerical simulations [18,19] suggest that for δ ∼ −0.8 the typical void size tends to be around ∼ 10h −1 Mpc. This means that a ∼ 100 − 200h −1 Mpc void is extremely unlikely to form in the concordance cosmology.…”
Section: Lensing By the Voidmentioning
confidence: 99%